Biodemographic parameters of spodoptera frugiperda smith, 1797 (Lepidoptera: Noctuidae), a pest of maize crop, zea mays linnaeus, 1753 in sub-sudanese zone of Côte d'Ivoire - Konan, Stephanie Manuela Klamansoni Akissi; Kansaye, Laya; Dakouri, Henoc Jacques Meva; Aboua, Nondenot Roi Louis (International Research Journal of Insect Sciences, 2023)
Spodoptera frugiperda is one of the main pests of maize (Zea mays L.) in Côte d'Ivoire. The control of this insect requires knowledge of biological and demographic parameters. The need to know the effect of seasons on the biodemographic parameters of Spodoptera frugiperda in Côte d'Ivoire led us to carry out work in the Sub-sudanese zone. The study was carried out in dry and rainy seasons on a maize plot from 2020 to 2021. The monitoring of newly emerged individuals on 3-week-old early variety with semi-serrated grains (EV 87/28-SR) maize plants under semi-natural conditions. The development cycle consisted of six larva stages. The development time was 27.93 ± 1.01 days in dry season and 32.47 ± 1.83 days in rainy season. Larval survival rates ranged from 85.79 to 100% in dry season and from 74.64 to 94.7% in rainy season. The average egg fertility rate was 21.19 ± 5.89% in dry season and 40.36 ± 8.49% in rainy season. The sex ratio was in favour of females. The net reproduction rate (Ro) and intrinsic rate of natural increase (rm) were highest in rainy season at 27.67 ± 7.82 and 0.26 ± 0.01 respectively. Spodoptera frugiperda performs much better in rainy season at temperatures between 25.1°C - 26.2°C due to a slow development time of 32.47 ± 1.83 days, a short population doubling time (D.T.) of 2.62 ± 0.13 and a high net reproduction rate (Ro) of 27.67 ± 7.82.